Assessment of internal exposure to methylsiloxanes in children and associated non-dietary exposure risk - Guo, J.; Y. Zhou; Y. Wang; B. Zhang; J. Zhang (Environment International, 2021)
Methylsiloxanes (MSs) are a significant source of indoor environmental pollution due to their high production level and widespread application, and pose a potential health risk. Given the special vulnerability of children to environmental contaminants, assessment of indoor MSs exposure in children is quite essential. In this study, we assessed internal exposure doses and external exposure levels of MSs in children from industrial and residential areas in southwestern China. Indoor air, indoor dust, and personal care product (PCP) samples were collected to evaluate indoor non-dietary MSs exposure in children through various pathways. The concentrations of MSs in indoor environments of industrial areas were approximately one to four orders of magnitude higher than those of residential areas. Sun protection products contained the highest concentrations of MSs. Relatively high levels of cyclic methylsiloxanes (CMSs) were found in plasma of children from industrial areas, which were one to two orders of magnitude higher than those in children from residential areas. The highest MSs levels in plasma were detected in infants (0–1 year), with values of 1.4 × 102 ng/mL and 1.3 × 102 ng/mL for CMSs (D4–D6) and linear methylsiloxanes (LMSs) (L5–L16), respectively. The internal exposure dose of infants in residential areas is driven by major unknown sources of MSs. The average daily doses via inhalation and dust ingestion in children from industrial areas were one to three orders of magnitude higher than in those from residential areas, indicating that these children should be considered a highly exposed population. Inhalation and dust ingestion were both major exposure pathways to MSs for children of all age groups in industrial areas, whereas dermal absorption from PCPs was the predominant exposure pathway for children of all age groups in residential areas (except for infants). Although the exposure risk to D4 and D5 was at an acceptable level for all children studied, the total daily exposure doses of these two cyclic compounds via inhalation for infants in the industrial areas was near the chronic reference dose. Meanwhile, MSs may accumulate in infant plasma within a short period of time (<6 months). Therefore, infants should be the focus of greater attention in future research. As indoor environments may pose high risks for infants in industrial areas, they should be the focus of future research. © 2021
Keywords: absorption; air pollution; ambient air; article; attention; case report; Child; Child exposure; child health; China; clinical article; concentration (composition); dust; Dust ingestion; environmental exposure; Environmental Monitoring; Exposure dose; Exposure pathways; Female; groups by age; health risk; Health risks; Housing; human; human tissue; Humans; Indoor; indoor air; indoor air pollution; Indoor environment; Industrial area; Industrial research; Infant; ingestion; Internal exposure; Male; Methylsiloxane; Orders of magnitude; plasma; pollutant source; pollution exposure; residential area; Residential areas; Risk Assessment; Silicon; Silicon compounds; siloxane; Siloxanes; skin absorption; sun